2020
DOI: 10.1002/jbmr.4709
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Randomized Controlled Trial With Low-Dose B-Vitamin Supplementation Shows Benefits on Bone Mineral Density in Adults With Lower B12 Status

Abstract: Folate, vitamins B12, B6, and riboflavin are required for one‐carbon metabolism and may affect bone health, but no previous randomized trial has investigated all four nutrients in this context. We investigated the effect of low‐dose B‐vitamins for 2 years on bone mineral density (BMD) in a dual‐centered, 2‐year randomized controlled trial (RCT) in adults aged ≥50 years. Eligible participants not consuming B‐vitamin supplements or fortified foods >4 times weekly were randomized to receive daily either combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Additionally, the folic acid status may be affected by other factors—not only diet—such as the gut microbiota [ 44 ] or inflammation, which also may affect nutritional status [ 45 ]. Clements et al reported that low-dose vitamin B (folate, vitamins B2, B6, and B12) supplementation for two years did not affect the BMD in adults over 50 years old [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the folic acid status may be affected by other factors—not only diet—such as the gut microbiota [ 44 ] or inflammation, which also may affect nutritional status [ 45 ]. Clements et al reported that low-dose vitamin B (folate, vitamins B2, B6, and B12) supplementation for two years did not affect the BMD in adults over 50 years old [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis may also have been underpowered to detect differences in serum PTH between PPI groups. Of interest, higher dose PPI use has been associated with vitamin B12 deficiency (through suppression of gastric acid secretion) [ 27 ], while supplementation of B12-deficient individuals with B vitamins may increase BMD [ 22 ]. However, no study has shown any association between hyperparathyroidism and serum B vitamin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which PPIs contribute to fracture risk are currently unknown, but a number of ideas have been postulated including inhibition of gastric acid secretion and reduced absorption of calcium and other nutrients (e.g., B vitamins) which may be important for bone health and hypergastrinaemia [ 8 , 9 , 22 ]. However, only a few small studies have previously explored the relationship between PPIs and serum PTH [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated combined group B vitamin supplementation. It was previously demonstrated shown that the 2-year group B vitamin (folic acid, B 6 , B 12 , B 2 ) supplementation in subjects with a low B 12 status prevented a significant reduction in BMD at the femoral neck and hip ( 280 ). In turn, circulating plasma folic acid and B12 levels have been shown to be directly associated with BMD and bone strength in post-menopausal Chinese-Singaporean women, respectively ( 281 ).…”
Section: Group B Vitaminsmentioning
confidence: 99%